A descriptive study of randomised trials of treatments for childhood acute lymphoblastic leukaemia - Burrett, J; Clarke, M (Wiley, 2002)
This report presents a historical and descriptive account of randomised trials in childhood leukaemia since the earliest such studies in the 1960s. It focuses on trials that began before 1988 making use of the register of trials developed for a systematic review of treatments for acute lymphoblastic leukaemia in children. The number of randomised trials starting each year has increased from one or two in the 1960s to an annual average of five or six in the 1980s. However trials remained relatively small, with more than half of all randomisations accruing less than 200 patients, and only five having more than 1000. Most trials were published more than once.